Une mesure composite du risque des prêts hypothécaires - Chung, Joseph; To, Minh; Thrin, Minh (L'Actualité économique, 1982)
AbstractIn this study, a cardinal and continuous measure of the default risk of mortgage loans is proposed, in departure from past studies where that risk was measured by dichotomous or categorical variables. The cardinal and continuous measure of risk is obtained by use of the canonical factor analytic technique. The unique factor of risk is a linear combination of the rate of return on equity, of the break-even rental income and of the vacancy rate of the property, and also of the relative term of the mortgage loans. It is found that the default risk of mortgage loans is well explained by the attributes of the property and of the neighbourhood, as well as by the location and the mortgage ratio. Furthermore, the buyer seems to incur hidden transaction costs which increase his risk level over that observed of the seller.